2013
DOI: 10.1002/cam4.84
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival disparities by health insurance status

Abstract: Previous studies found that uninsured and Medicaid insured cancer patients have poorer outcomes than cancer patients with private insurance. We examined the association between health insurance status and survival of New Jersey patients 18–64 diagnosed with seven common cancers during 1999–2004. Hazard ratios (HRs) with 95% confidence intervals for 5-year cause-specific survival were calculated from Cox proportional hazards regression models; health insurance status was the primary predictor with adjustment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
156
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(175 citation statements)
references
References 32 publications
13
156
2
4
Order By: Relevance
“…In contrast to our data, the authors only looked at patients of age 18 -64 years and follow-up was limited to one year. Similar studies using statewide registries have found that patients with colorectal cancer who were uninsured or had medicaid, had a higher risk of death compared to private insurance [20] [25] [26]. These studies, however, did not consistently adjust for SES or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to our data, the authors only looked at patients of age 18 -64 years and follow-up was limited to one year. Similar studies using statewide registries have found that patients with colorectal cancer who were uninsured or had medicaid, had a higher risk of death compared to private insurance [20] [25] [26]. These studies, however, did not consistently adjust for SES or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in an equal access system, the Veteran's Administration, outcomes disparities across racial lines are significantly diminished [12] [14]. It is likely that poorer outcomes for AA are, in part, secondary to unequal use of screening, surgical resection, adjuvant therapy and appropriate follow-up [13] [16]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…11 In a prospective cohort study in the United Kingdom, Ramsay and colleagues 12 investigated the same time trend by social class, defined by occupation, among 7489 men and observed no change in the association between cancer survival and occupation during their 35-year follow-up period. In the US, Niu and colleagues 13 examined whether the disparity in cancer survival by insurance status changed between 1999 and 2004 and found that survival improved for privately insured patients but not for those insured by Medicaid. The objective of the current study was to determine whether the magnitude of the association between socioeconomic status and cancer survival changed between 1993 and 2009 in Ontario.…”
mentioning
confidence: 99%
“…[14][15][16][17] In the United States, women without insurance or with Medicaid showed lower survival rates. 15,18,19 In addition, lower education, greater distance between the patient's home and the hospital where women receive health care and delay in starting treatment have been, also associated with larger tumors. 20,21 This study assess the effect of health care delays: from the first symptoms to the first contact with a doctor, from receipt of mammography results to receipt of diagnostic biopsy results, and from diagnosis to the initiation of treatment, on five-year survival.…”
mentioning
confidence: 99%